Identitas dan Toleransi: Konsep Utama dalam Rethinking Multiculturalism - Rachmat Panca Putera (Pusat Riset dan Inovasi Nasional, 2024)
This research examines the concepts of identity and tolerance within the context of multiculturalism, focusing on the ideas of Bhikhu Parekh. The background of this study stems from the increasing complexity of social interactions in multicultural societies, where individual and group identities continue to evolve. The objective of this research is to analyze how identity is formed in multicultural societies and the role of tolerance in addressing potential conflicts. The methodology employed is a qualitative approach through literature analysis, reviewing Parekh's works and other relevant sources. The findings indicate that identity is not a static entity but rather a result of dynamic social interactions. Furthermore, tolerance is viewed as a crucial solution in alleviating tensions between groups. The implications of this research emphasize the need for inclusive public policies that promote intercultural dialogue and protect individual rights without neglecting community values. Consequently, this study contributes to the understanding of the importance of identity and tolerance in creating harmonious societies.